Translating Arabic Culture-Bound Terms (CBTs) into English: A Pilot Study of Translation Students’ Challenges and Strategies - Sofiene Tergui; Abdul Mutalib Bin Embong; Che Wan Ida Rahimah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
In the current research, the focus is on exploring some of the most common translation problems encountered by undergraduate translation students when translating Arabic culture-bound terms (henceforth referred to as CBTs) into English. The mentioned terms pose serious obstacles to translation, as they carry complex cultural connotations and cannot be regarded as equivalents in other languages. Based on existing translation theories by scholars such as Peter Newmark and Mona Baker, this study aims to define the nature of the aforementioned problems and the ways undergraduates can solve them. This study is exploratory and serves as a pilot for a larger-scale investigation. Thus, the chosen methodology was of the same nature and included a sample of 30 undergraduate translation students who translated 10 Arabic statements containing culture-bound terms into English. The data collected from the students were analyzed using the thematic analysis framework proposed by Newmark (1988). In particular, he proposed defining categories that include various cultural objects in accordance with Peter Newmark's classification. Then the chosen expressions were assigned to the appropriate categories, while their translation difficulties were identified with respect to the three mentioned aspects: semantic accuracy, syntactic appropriateness, and cultural adequacy. According to the findings from this sample, students face a significant challenge in retaining the cultural meaning when translating culture-bound expressions. They translate them using literal translation or partial equivalence, thus losing meaning and cultural essence. Moreover, the findings show that students prefer foreignization over domestication, with 67% preferring foreignization and 33% domestication. This is mainly because of their lack of understanding of the target culture.